LEADERSHIP STRATEGIES IN OPTIMISING THE QUALITY OF QUR'AN MEMORISATION LEARNING AT MUHAMMADIYAH 38 MEDAN KRIO PRIVATE PRIMARY SCHOOL - Tanjung, Jainuddin; Harahap, Hotni Sari; Hidayah, Nurul (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This This research aims to analyze the leadership strategies of the principal in improving the quality of Tahfizh learning at SD Swasta Muhammadiyah 38 Medan Krio, as well as the obstacles faced in its management. The study uses a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participatory observation, and documentation. The obtained data were analyzed using thematic data analysis to identify key patterns from interviews and observations, and to categorize findings according to the research objectives. Based on the research results, the principal’s leadership strategies to enhance Tahfizh learning quality are carried out through democratic, participative, and transformative approaches. The principal actively serves as an educator, leader, innovator, and motivator by designing various programs, such as teacher training, daily muraja’ah and ziyadah routines, integration of Qur’anic values into general subjects, and utilization of digital technology as a learning medium. These strategies have proven successful in creating a learning ecosystem that not only improves students’ memorization achievements but also holistically shapes their Qur’anic character. However, in implementation, several obstacles are faced by the principal, namely limited pedagogical competence of teachers, challenges in facilities and supporting devices, inconsistency in students’ memorization, as well as psychological pressures and external disturbances such as gadget use. These obstacles require a collaborative solution-based approach between the school, teachers, and parents, as well as continuous training to improve teaching quality. In addition, strengthening a learning culture that supports spiritual development and students’ motivation needs to be carried out continuously to achieve optimal results in Tahfizh learning.